The impact of disease activity and tumour necrosis factor‐α inhibitor therapy on cytokine levels in juvenile idiopathic arthritis. (13th April 2016) - Walters, H. M.; Pan, N.; Lehman, T. J. A.; Adams, A.; Kalliolias, G. D.; Zhu, Y. S.; Santiago, F.; Nguyen, J.; Sitaras, L.; Cunningham‐Rundles, S.; Walsh, T. J.; Toussi, S. S.
Summary: The aim of this study was to evaluate prospectively cytokine levels and disease activity in juvenile idiopathic arthritis (JIA) patients treated with and without tumour necrosis factor (TNF)‐α inhibitors. TNF‐α inhibitor‐naive JIA subjects were followed prospectively for 6 months. Cytokine levels of TNF‐α, interleukin (IL)−1β, IL‐6, IL‐8, IL‐10 and IL‐17 were measured at baseline for JIA subjects and healthy controls (HCs). Cytokine levels were then measured at four time‐points after initiation of TNF‐α inhibition for anti‐TNF‐α‐treated (anti‐TNF) JIA subjects, and at two subsequent time‐points for other JIA (non‐TNF) subjects. JIA disease activity by Childhood Health Assessment Questionnaire (CHAQ) disability index/pain score and physician joint count/global assessment was recorded. Sixteen anti‐TNF, 31 non‐TNF and 16 HCs were analysed. Among JIA subjects, those with higher baseline disease activity (subsequent anti‐TNFs) had higher baseline TNF‐α, IL‐6 and IL‐8 than those with lower disease activity (non‐TNFs) ( P  < 0·05). TNF‐α and IL‐10 increased, and IL‐6 and IL‐8 no longer remained significantly higher after TNF‐α inhibitor initiation in anti‐TNF subjects. Subgroup analysis of etanercept versus adalimumab‐treated subjects showed that TNF‐α and IL‐17 increased significantly in etanercept but not adalimumab‐treated subjects, despite clinical improvement in both groups of subjects. JIA subjects with increased disease activity at baseline had higher serum proinflammatory cytokines. TNF‐α inhibition resulted in suppression of IL‐6 and IL‐8 in parallel with clinical improvement in all anti‐TNF‐treated subjects, but was also associated with elevated TNF‐α and IL‐17 in etanercept‐treated subjects.